Work Motivation and Employee Engagement in Digital Work Environments: A Systematic Literature Review - Nurrohmi Handayani; Sanie Febriyanti; Mirwan Surya Pradana (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The rise of digital technologies has transformed how organizations operate and interact with their employees. This study examines the role of work motivation and employee engagement in shaping performance outcomes within digital work environments. Conducting a systematic literature review of 30 peer-reviewed articles published between 2000 and 2025, this study synthesizes theoretical and empirical findings to identify how motivation translates into performance under digitally mediated conditions. The analysis shows that autonomy, psychological empowerment, and meaningful work function as primary motivational drivers, while employee engagement operates as a key mediating mechanism linking motivation to performance. Performance outcomes in digital contexts are characterized not only by productivity but also by adaptability, collaborative effectiveness, and innovation capacity. The evidence further indicates that digital leadership and organizational agility strengthen the motivation–engagement–performance pathway, whereas technostress and role ambiguity weaken it. These findings contribute to a more integrated understanding of human-centered performance dynamics in digital organizations and offer strategic implications for developing supportive digital work environments.